Enhancing digital literacy in primary education through augmented reality - Nevrelova, Natalie; Korenova, Lilla; Lavicza, Zsolt; Bruzkova, Nikola; Schmid, Angelika (Frontiers in Education, 2024)
Currently, there is a need to develop digital competencies already because they are included in the new curriculum. This article explores the field of augmented reality (AR) and its educational potential to bolster digital literacy in primary education. The core objective is to scrutinize the suitable use of AR-integrated mobile applications in primary schooling, spotlighting widely adopted apps and their practical applications. The article underscores digital literacy as a key competence for children’s self-directed future learning. In our research we used a combination of qualitative and quantitative research approaches. It seeks to identify the impacts and benefits of AR in primary school settings. In a natural didactic context, it is conducted as action research. The methodology includes direct observation of pupils engaging with the AR app Quiver during educational tasks, complemented by discussions with their teacher as a focus group. Additionally, the study gathers insights from parents via questionnaires based on their perceptions of AR in education. The analysis of the interview data utilizes the open coding technique to interpret the findings. The relevance of the research was confirmed by the consistency of results when transitioning from onsite to online learning environments. The study showed that AR engagement helped to increase the digital literacy of the participating pupils, showing high levels of engagement, motivation and collaborative communication.